Case Report: A Calculus-Free Ureteral Stent Forgotten for 29 Years - Tang, Cheng; Qu, Genyi; Yang, Guang; Wang, Gang; Xu, Yong (Frontiers in Surgery, 2022)
Ureteral stents are widely used. If the ureteral stents remain in place for extended periods, the probability of migration and stone formation increases substantially. However, a 29-year-old ureteral stent placed that does not develop calculus is rare. We reported a 45-year-old man admitted with pain in his left waist and abdomen for more than ten years. He underwent ureterotomy 29 years prior to admission for left ureteral calculi, and a ureteral stent was placed postoperatively to prevent ureteral strictures. The ureteral stent was not removed in hospital due to poor compliance on the part of the patient. This left ureteral stent was not visible on computed tomography and plain films. On ureteroscopy or flexible ureteroscopy, no new calculus was found in the left ureter and kidney. No calculus was found in the stent easily removed with calculus-removing forceps. This phenomenon is rare, and it highlights the importance of follow-up.